Impact of diversified cropping system on primary nutrients and crop yield in north-western Himalayas - Mandial, Avnee; Negi, S C (Journal of Cereal Research, 2023)
Crop diversification is one of the sustainable approaches to maintain soil fertility along with productivity. A field experiment was conducted during 2017-18 at Bhadiarkhar research farm, Department of Agronomy, CSKHPKV, Palampur to evaluate the impact of diversified cropping system on primary nutrients and crop yield of eight rice-based crop sequences viz. rice – wheat, rice – pea – summer squash, okra – radish – onion, turmeric – pea – summer squash, rice – lettuce – potato + coriander, rice – palak – cucumber, rice – broccoli – radish and Colocasia – pea + coriander. The experiment was laid out in randomized block design and was replicated four times. The results showed that rice – wheat sequence resulted in highest nitrogen, phosphorus and potassium uptake. Nutrient mining (N, P and K) was recorded after the completion of the crop cycle although loss was maximum from the system where more nutrients were added.